Development of na HPLC–MS/MS method for the determination of ginsenosides Rg1 and Rb1 from 'Shenmai' Injection in beagle dogs after single and multiple doses and application in pharmacokinetics. (3rd January 2023) - Wen, Min; Yang, Lipan; Huang, Hefei; Ye, Gu; Jiang, Yuntao; Lv, Xiaobo
Abstract: Shenmai Injection (SMI), which tonifies Qi and prevents exhaustion, nourishes Yin and generates body fluid, is usually used in the treatment of shock with deficiency of Qi and Yin, coronary artery disease, viral myocarditis, granulocytopenia and chronic pulmonary heart disease clinically. Ginsenosides Rg1 and Rb1 are the main active ingredients of SMI. In this study, high‐performance liquid chromatography tandem mass spectrometry methods for quantification of Rb1 and Rg1 in beagle dogs were developed and validated according to international regulatory guidelines. The methods were applied to measure the pharmacokinetics parameters of the two ginsenoside after intravenous administration. The linear ranges of the analytes were 3.9–1, 000 ng/ml for Rg1 and Rb1. After injection of single and multiple doses of SMI (1 ml/kg), the plasma concentration–time profiles of Rg1 and Rb1 met the characteristics of one‐compartment and typical two‐compartment intravenous injection.